CCSP certified cloud security professional exam guide - Carter, Daniel, CISSP (All-in-one (Series), 2020)
"This highly effective self-study guide covers all six domains of the 2019 release of the challenging Certified Cloud Security Professional exam as well as the CCSP Common Body of Knowledge, developed by the International Information Systems Security Certification Consortium (ISC)²"--